Ethical Foundations of Scientific Publishing - Özen, Fatmanur; Demircioğlu, Aytekin (IGI Global, 2024)
Publishing ethics govern the behavior of individuals and organizations involved in disseminating research, crucial for maintaining the integrity and credibility of the academic corpus. Adherence to ethical principles in scientific publications is vital for upholding research integrity, fostering trust, and advancing scientific knowledge. International organizations enforce these ethics, formulating guidelines and overseeing practices. This section introduces global publication ethics committees, explores Türkiye's national practices, and discusses measures to enhance scientific publication quality. The chapter identifies publication ethics violations in Türkiye, concluding with recommendations to mitigate transgressions.
Keywords: 4. Education; 16. Peace & justice